Effect of Triton, HEDP and EDTA chelating irrigant’s protocol on micro-hardness of root canal dentine: An in vitro study (Mustansiria Dental Journal, 2025)
Aim: To assess and compare the effectiveness of different chelating irrigants (Triton, 1-hydroxyethylidene-1,1-bisphosphonate (HEDP) for continuous chelation, and 5.25% NaOCl+17% ethylenediaminetetraacetic acid (EDTA)) for conventional chelation on root canal dentine micro-hardness.Materials and methods: Forty mandibular premolars extracted for orthodontic reason were used in this study, teeth were then divided into four groups according to type of irrigation solution, Group A; Triton, Group B; HEDP, Group C; EDTA, Group D; Distilled water (control). The crowns removed to produce root length of 14 mm, all teeth prepared using ProTaper Next files up to size 40/0.06. Then the roots separated into two parts. The microhardness evaluated at three thirds (coronal, middle, and apical) for each half, 3 N load was used for 15s. The data were statistically analyzed using one-way ANOVA and Tukey post hoc test. The level of significance was set at p ≤ 0.05.Results: Triton had the least effect on micro-hardness, while EDTA had the highest effect. All chelating agents in this study reduced micro-hardness with no significant difference between them, but significantly different from the control group (p ≤ 0.05) at coronal third.Conclusion: All chelating agents reduced micro-hardness at three thirds.